A Study of Opinion of Parents towards International School Education in Ahmedabad City in Relation to Certain Variables: - (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Present study was under taken to know the opinions of Parents towards International School Education of Ahmedabad in context to Gender, Qualification and Profession .Null hypothesis was formed to know the effect of the variables. Present study is limited to parents of Ahmedabad. Total 250 parents were selected by using stratified random sampling method. Descriptive survey method was used to collect data by using self-prepared and standardized opinionative. Data was analyzed using Mean, Standard Deviation and t-test. Gender, Qualification and Profession were not affecting variables on the opinion of parents on International School Education.